Mendorong Kemajuan Ekonomi dan Sosial Desa melalui Inovasi Perpustakaan Digital Pada Desa Sukaraja Lampung Selatan - Lukman Nuzul Hakim; Umar Sanusi; M. Fajar Shiddiq; Isna Wardah (MUHKAL, 2024)
The village of Sukaraja, South Lampung, faces challenges in improving the economic and social welfare of its community. The innovation of a digital library was introduced as a solution to overcome the limitations of access to information and education. This study aims to examine the impact of the digital library on the economic and social progress in Sukaraja Village. The research methodology includes observations, interviews, and surveys of the village residents. The research results show that the digital library has increased literacy, provided access to economic information, and supported social activities. The implementation of the digital library has encouraged the enhancement of residents' skills and knowledge, contributing to the economic and social development of the village.